A possibilidade de construção de uma moralidade política em Hannah Arendt - Müller, Maria Cristina (Universidade Federal de São Carlos, 2010)
May it be possible, based on Hannah Arendt s thoughts, to think of a morality built on the perspective of the subject and not on submission to absolute and abstract norms, a subject that, even in his singularity, continues linked to the political realm? The pertinence of the interrogation is found in a both moral and political problem: the inability of those who lived under a totalitarian regime such as the Nazi to tell right from wrong. Human capacity to commit indignities and cruelties against other human beings, characteristic of the Nazi society, is the background from which the issue under study arose. Arendt s response derives from her perception of the absence of thinking, understood as a silent dialogue between me and myself and, consequently, be able to judge right from wrong, individually taking responsibility for the surrounding world one is an integral part of. It was clear to her that she should address the debate on morality. Thus, the investigation of contemplative activities and their relation with the sphere of action becomes imperious. The challenge Arendt proposes is to think of a morality that preserves individuality, both respecting it and connecting to the sphere of human action, in the attempt to come to terms with the perplexities the contemporary world had imprinted on her. It is in this sense that the term political morality is used, namely, that the subject thinks individually but the result of his thinking appears in the public sphere in the form of his judgment at the moment the citizen acts based on his own choices and not guided by any absolute and abstract principles and laws. Thus the individual would judge the question of right and wrong without reference to previously given absolute universals but the others: those who one wants to live with. Judging is connected to worldliness once the individual shows the world his opinions, thus constituting a singularity in the public space. The capacity of judging renders dignity to human beings as they can take part in such public space as singular beings: subjects. The human being is an agent, born to begin, free to begin, because he can choose. This beginning of something new is initiated in the realms of interiority, but only gains meaning and is actualized in the public realm together with many other I s. Therefore, the activities of the mind need appear and act in concert.
Keywords: Filosofia alemã; Arendt, Hannah, 1906-1975; Moralidade; Política; Singularidade; Mundo público; Pensar; Querer; Julgar; Ação; Hannah Arendt; Morality; Politics; Singularity; Public sphere; Thinking; Willing; Judging; Action; CIENCIAS HUMANAS::FILOSOFIA